Middle French: When? What? Why? - Smith, J (Elsevier, 2002)
The so-called 'Middle French' period has been variously dated on the basis of a number of internal and external phenomena. This paper examines the linguistic criteria which have been adduced, concludes that there is no real discontinuity which serves to define 'Middle French', and, following Coseriu's work on synthetic and analytic exponence in Romance, as well as recent arguments of Lass concerning the nature of periodization, suggests that the value of the concept of 'Middle French' may be essentially typological rather than temporal - specifically, that it defines a variety of French which broadly conforms to the Romance morphosyntactic 'prototype', as represented by Spanish and Italian.